2019
DOI: 10.3126/ojn.v9i1.25692
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric Approach to Vertical Facial Height

Abstract: Introduction: The vertical heights and the proportions are very important for balance of the face and attractiveness along with the good smile. Harmonious vertical proportions and the Antero-posterior relations contribute to aesthetics. Therefore it is necessary to determine the vertical facial height and the ratios in treatment planning of the patients. The aims and objectives of this study are to compare the vertical facial heights of patients considering the Lower Anterior Facial Height (LAFH), the Upper An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…The mean posterior facial height of female was less when compared to male to result obtained by Maskey and Shrestha, 20 Taner et al 21 Wang et al 22 found that PFH rather than AFH play a key role in the vertical facial type. This was true in the present study too, but only in hypodivergent group, as PFH was correlated to Jarabak ratio only in hypodivergent group.…”
Section: Resultsmentioning
confidence: 73%
“…The mean posterior facial height of female was less when compared to male to result obtained by Maskey and Shrestha, 20 Taner et al 21 Wang et al 22 found that PFH rather than AFH play a key role in the vertical facial type. This was true in the present study too, but only in hypodivergent group, as PFH was correlated to Jarabak ratio only in hypodivergent group.…”
Section: Resultsmentioning
confidence: 73%
“…In our study the mean value of UAFH and LAFH in males and females don't show significant differences. Previous studies [12][13][14][15] have also shown no significant differences between male and female.…”
Section: Discussionmentioning
confidence: 80%
“…Evaluation of the vertical patterns and proportions has a major role in the overall harmony of the face. [ 17 ] Vertical dimensions include Anterior Facial Height (AFH) and Posterior Facial Height (PFH). Anterior Facial Height (AFH) is divided into upper anterior facial height (UAFH) and lower anterior facial height (LAFH).…”
Section: Discussionmentioning
confidence: 99%